78.9k views
2 votes
Find the solution c+(4-3c)-2=0

User Rakefet
by
5.5k points

2 Answers

3 votes
so you can combine c and -3c to get -2c. The equation then is -2c + 4 - 2 = 0.
then you can combine 4 and -2 to get 2 so now the equation is -2c + 2 = 0. Now you want the 2 on the other side to solve for c so you would subtract 2 to the other side. -2c = -2. divide both sides by -2 and c = 1.
Hope this helps!
User Fred Campos
by
5.0k points
5 votes
c=1 is the answer my good man have a good day :)
User Galaxy
by
5.2k points